IMPLEMENTASI LAYANAN BIMBINGAN KLASIKAL DALAM MEMBERIKAN PEMAHAMAN MENGENAI DAMPAK PROKRASTINASI AKADEMIK - Chotimah, Chusnul; Bunyamin, Bunyamin (Fakultas Ushuluddin, Adab, dan Dakwah UIN Sultan Aji Muhammad Idris Samarinda, 2023)
The form of procrastination that they practice is avoiding assignments that have been given by the subject teacher, finding it difficult to understand the material that has been explained by the subject teacher, and delaying when doing assignments so that when the task will be collected, the students concerned are not present during class time. This research method uses a descriptive qualitative research design. The data sources for this research are guidance and counseling teachers, three students who have received classical guidance services, school principals, and subject teachers. Data collection techniques using interviews and documentation The data validation technique uses source triangulation. The data obtained was analyzed using the Miles, Huberman, and Saldana models, which included data collection, data condensation, data display, and drawing and verifying conclusions.The results showed that the classical guidance services provided by counseling teachers had three aspects: the preparatory aspect, which included preparing the topic of classical guidance material and compiling RPL; the implementation aspect, which included carrying out classical guidance services according to schedule and providing services according to the material that had been prepared; and the outcome aspect, which includes process evaluation and outcome evaluation after the service is implemented.